2021
DOI: 10.1186/s40249-021-00800-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal visualization for the global COVID-19 surveillance by balloon chart

Abstract: Background Considering the widespread of coronavirus disease 2019 (COVID-19) pandemic in the world, it is important to understand the spatiotemporal development of the pandemic. In this study, we aimed to visualize time-associated alterations of COVID-19 in the context of continents and countries. Methods Using COVID-19 case and death data from February to December 2020 offered by Johns Hopkins University, we generated time-associated balloon chart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Task Accuracy User Experience Task Efficiency N/A [14,16,18,22,24,[27][28][29][30][32][33][34][35][37][38][39][41][42][43][44][45][46][47]49,[52][53][54][55][56][57][58][59]61,64,65,[68][69][70]72,73,[75][76][77][78][79][81][82][83][84][85][86][87]…”
Section: Papers Standard Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Task Accuracy User Experience Task Efficiency N/A [14,16,18,22,24,[27][28][29][30][32][33][34][35][37][38][39][41][42][43][44][45][46][47]49,[52][53][54][55][56][57][58][59]61,64,65,[68][69][70]72,73,[75][76][77][78][79][81][82][83][84][85][86][87]…”
Section: Papers Standard Methodologymentioning
confidence: 99%
“…With regard to datasets, 72.81% (83/114) of the studies indicated which ones they used. However, owing to the extent and variety of the studies reviewed, there were only eight duplicate sources: Korea Centers for Disease Control & Prevention (KCDC) [30,44,71,106,107], Johns Hopkins University datasets [15,23,28,42,46,47,53,57,75,81,[84][85][86]95,97,98,125], WHO COVID-19 Daily Report [30,42,43,76,102], European Centre of Disease Prevention and Control (ECDC) [57,86,100,108,118], Centre of Disease Prevention and Control (CDC) on COVID-19 [24,30,31,55,95,102], the National Health Commission [42,43,52,55,87], the US Census Bureau [31,46,49,…”
Section: Papers Standard Methodologymentioning
confidence: 99%
“…KIM et al, 2021;SCARPONE et al, 2020;KWOK et al, 2021;BUJA et al, 2020;VAZ, 2021). Como exemplo, tem-se a pesquisa de Lenzen et al (2020) BHERWANI et al, 2021;ZHANG et al, 2020;SANGIORGIO;PARISI, 2020;GIANQUINTIERI et al, 2020;POURGHASEMI et al, 2020;SHAW et al, 2021;KARAIVANOV, 2020;PAPASTEFANOPOULOS;VICTOR OKHUESE, 2020;LINARDATOS;KOTSIANTIS, 2020;CHENG et al, 2020;CHINAZZI et al, 2020;KONICEK et al, 2020;JIANG et al, 2020;PANG et al, 2021;ZHOU et al, 2020).…”
Section: A Dimensão Socialunclassified
“…Many studies on the spatial aspects of the Covid-19 case have been carried out around the world (Ballesteros et al, 2021;Edriani et al, 2021;Hu et al, 2021;Lak et al, 2021;Mohammad Ebrahimi et al, 2021;Pang et al, 2021;Purwanto et al, 2021;Raymundo et al, 2021;Saavedra et al, 2021). Not much has been done to study the spatial aspects of the Indonesian Covid-19 case (Dhewantara et al, 2022;Heldayani et al, 2021;Iriany et al, 2021;Ratnasari & Dewi, 2021).…”
Section: Introductionmentioning
confidence: 99%